Sociophysics A Physicist's Modeling of Psycho-political Phenomena - Galam, Serge; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Do humans behave much like atoms? Sociophysics, which uses tools and concepts from the physics of disordered matter to describe some aspects of social and political behavior, answers in the affirmative. But advocating the use of models from the physical sciences to understand human behavior could be perceived as tantamount to dismissing the existence of human free will and also enabling those seeking manipulative skills. This thought-provoking book argues it is just the contrary. Indeed, future developments and evaluation will either show sociophyics to be inadequate, thus supporting the hypothesis that people can primarily be considered to be free agents, or valid, thus opening the path to a radically different vision of society and personal responsibility. This book attempts to explain why and how humans behave much like atoms, at least in some aspects of their collective lives, and then proposes how this knowledge can serve as a unique key to a dramatic leap forwards in achieving more social freedom in the real world. At heart, sociophysics and this book are about better comprehending the richness and potential of our social interaction, and so distancing ourselves from inanimate atoms.
Part 1: Sociophysics: setting the frame -- What is sociophysics about? -- The question: do humans behave like atoms? -- Sociophysics: the origins -- Sociophysics: weaknesses, achievements and challenges -- Part II: Discovering the wonderful (and maybe scary) world of Sociophysics -- Sociophysics: an overview of emblematic founding models -- Universal features of group decision making -- The dictatorship paradox of democratic bottom-up voting -- The dynamics of spontaneous coalition-fragmentation versus global coalitions -- Terrorism and the percolation of passive supporters -- The modeling of opinion dynamics -- By way of caution -- Part III: Democratic voting in bottom-up hierarchical structures: from advantages and setbacks to dictatorship paradoxes -- Highlights of the Part -- Basic mechanisms for the perfect democratic structure -- Going to applications -- Touching on a fundamental aspect of nature, both physical and human -- Dictatorship paradoxes of Democratic voting in hierarchical structures -- Part IV: The risky business of alliances in bottom-up democratic voting with three-choice competition -- Bottom-up democratic voting in a three-choice competition -- So sorry, that's the end of the tour! -- I thank you.
Keywords: Social sciences; Operations research; Decision making; Behavioral sciences; Game theory; Statistical physics; Dynamical systems; Economic theory; Social Sciences; Methodology of the Social Sciences; Statistical Physics, Dynamical Systems and Complexity; Behavioral Sciences; Game Theory, Economics, Social and Behav. Sciences; Operation Research/Decision Theory; Economic Theory/Quantitative Economics/Mathematical Methods; Electronic books